A case of superior vena cava syndrome misdiagnosed as angioedema - Ruimiao WU; Xia DOU (Pifu-xingbing zhenliaoxue zazhi, 2022)
A 67-year-old male presented facial erythema, swelling and paroxysmal chest tightness for more than 1 month. Dermatological examination revealed that edema erythema with unclear borders mainly over the periorbital, cheeks and varicose veins on the chest wall. There was no response to angioedema treatment with antihistamine and systemic glucocorticoid. Varicose veins on the chest wall were found. Chest CT showed superior mediastinal mass with involvement of superior vena cava. Histopathologic features and immunohistochemistry of the neck lymph node indicated small cell carcinoma. According to the result, the diagnosis of small cell carcinoma of mediastinum combined with superior vena cava syndrome was made. The patient was discharged from the hospital by himself and followed up by telephone six months later. The patient has passed away.